Dihydropyrimidinase protects from DNA replication stress caused by cytotoxic metabolites. Issue 4 (19th December 2019) - Basbous, Jihane; Aze, Antoine; Chaloin, Laurent; Lebdy, Rana; Hodroj, Dana; Ribeyre, Cyril; Larroque, Marion; Shepard, Caitlin; Kim, Baek; Pruvost, Alain; Moreaux, Jérôme; Maiorano, Domenico; et al.
Abstract: Imbalance in the level of the pyrimidine degradation products dihydrouracil and dihydrothymine is associated with cellular transformation and cancer progression. Dihydropyrimidines are degraded by dihydropyrimidinase (DHP), a zinc metalloenzyme that is upregulated in solid tumors but not in the corresponding normal tissues. How dihydropyrimidine metabolites affect cellular phenotypes remains elusive. Here we show that the accumulation of dihydropyrimidines induces the formation of DNA–protein crosslinks (DPCs) and causes DNA replication and transcriptional stress. We used Xenopus egg extracts to recapitulate DNA replication in vitro . We found that dihydropyrimidines interfere directly with the replication of both plasmid and chromosomal DNA. Furthermore, we show that the plant flavonoid dihydromyricetin inhibits human DHP activity. Cellular exposure to dihydromyricetin triggered DPCs-dependent DNA replication stress in cancer cells. This study defines dihydropyrimidines as potentially cytotoxic metabolites that may offer an opportunity for therapeutic-targeting of DHP activity in solid tumors.